1998
DOI: 10.1001/archderm.134.9.1101
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tacrolimus Is Not Effective in Chronic Plaque Psoriasis

Abstract: Background: Cyclosporine for the treatment of psoriasis constitutes a new approach. Alternative systemic cyclosporine derivatives have been studied to find an immunosuppressive drug with fewer adverse effects. Tacrolimus is one of these new immunosuppressive drugs. Systemically, it has been proven effective in treating psoriasis. A topical formulation of tacrolimus is attractive because it has fewer adverse effects and is useful for a large group of patients. We report for the first time on the efficacy of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
2
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 29 publications
1
92
2
8
Order By: Relevance
“…21 However, topical application of the commercial ointment failed to promote FK506 deposition in hyperkeratotic psoriatic plaques. 22 Meanwhile, FK506 ointment is difficult to be washed off from the skin surface and may create a sticky sense and discomfort to the patient due to its greasy nature. Several reports demonstrated that topical application of FK506 ointment was only effective under occlusion or to some specific regions of the body where the skin was thinner and more permeable, such as the face and intertriginous areas.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, topical application of the commercial ointment failed to promote FK506 deposition in hyperkeratotic psoriatic plaques. 22 Meanwhile, FK506 ointment is difficult to be washed off from the skin surface and may create a sticky sense and discomfort to the patient due to its greasy nature. Several reports demonstrated that topical application of FK506 ointment was only effective under occlusion or to some specific regions of the body where the skin was thinner and more permeable, such as the face and intertriginous areas.…”
Section: Introductionmentioning
confidence: 99%
“…There is one abstract indicating its efficacy in psoriasis when applied under occlusion (12). A controlled study could not detect efficacy in an open application approach (13). Ascomycin derivatives have also been tested for possible topical efficacy.…”
mentioning
confidence: 99%
“…Psoriasiste yapılan ilk randomize çalışmada takrolimusun plaseboya üstünlüğü gösterilememiştir 12 . Yazarlar bu sonucu ilacın günde bir kere ve oklüzyonsuz uygulanmasına bağlamıştır.…”
Section: Discussionunclassified
“…Psoriasiste topikal takrolimusun etkinliğinin değerlendirildiği çalışmalarda özellikle fasiyal, invers ve genital psoriasiste başarılı sonuçlar bildirilmiştir [5][6][7][8][9] . Bunun yanında kronik plak tipi psoriasiste etkinliği plaseboya benzer, plasebodan üstün ve potent steroidlere eşdeğer şeklinde çelişkili sonuçlar bildirilmektedir [10][11][12] . Son yıllarda topikal takrolimus tırnak tutulumunda da etkili olarak bildirilmiştir 13 .…”
Section: Introductionunclassified